Hubungan Pengetahuan Tentang Deteksi Dini Penyakit Degeneratif dengan Kejadian Hipertensi pada Lansia di Dusun Karangpucang Desa Ngancar Kecamatan Pitu - Maimunah, Siti (jurnal cakra medika, 2020)
The prevalence of hypertension which is increasing from year to year is no exception in the elderly, resulting in an increase in the health burden on the global community. The study was conducted to determine the relationship between knowledge about early detection of degenerative diseases and the incidence of hypertension in the elderly in Karangpucang Hamlet, Ngancar Village, Pitu District, Ngawi Regency. The research method applied is quantitative correlation with a cross sectional approach. The sample in this study was the elderly who took part in the elderly Posyandu activities in Karangpucang Village with a total of 54 elderly people using the total sampling method. The research instrument is a knowledge questionnaire about early detection of degenerative diseases. The analysis technique used the chi-square test,   with a confidence level of =0.05. The results of the study concluded that the level of knowledge of respondents about early detection of degenerative diseases was mostly in the sufficient category 24 (44.4%), and the results of measuring blood pressure in the elderly were mostly normal at 31 (57.4%). There is a relationship between knowledge about early detection of degenerative diseases and the incidence of hypertension in the elderly in Karangpucang Hamlet, Ngancar Village, Pitu District, Ngawi Regency with P = 0.023.